Nutrient solutions in the production of strawberry seedlings and their influence on agronomic performance - Schiavon, Andressa Vighi; Delazeri, Eloi Evandro; Becker, Tais Barbosa; Mello-Farias, Paulo; Antunes, Luís Eduardo Correa (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to evaluate the agronomic performance of strawberry cultivars established from plug plant plantlets produced with different nutrient solutions in a soilless system. The experiments were carried out in a greenhouse using seedlings of the Aromas and Camarosa cultivars, produced with four different nutrient solutions. Two cycles were evaluated. In the first, from April 2017 to March 2018, the agronomic performance of two cultivars (Camarosa and Aromas) and four nutrient solutions (NS1, NS2, NS3, and NS4) was assessed in a 2 x 4 factorial scheme. In the second cycle, from April to December 2018, two cultivars (Camarosa and Aromas) and two nutrients solutions (NS3 and NS4) were evaluated in a 2 x 2 factorial scheme. In both cycles, phenological, productive variables and the dry matter of leaves, crowns, and stolons were evaluated. The use of different nutrient solutions in the tip production stage did not influence most of the analyzed variables since the strawberry cycle is long, so their effects end up being diluted over time. However, the effect of the cultivar factor was significant, and, in general, the Camarosa cultivar was more precocious than the Aromas regarding the phenological variables related to flowering, fruiting, and tipping. The cultivars presented fruit production similar to each other in the two crop cycles, with Camarosa presenting greater production of dry matter of leaves and stolons than the Aromas cultivar.